Female pseudohermaphroditism in a prenatally diagnosed cloacal malformation with hydronephrosis, dilated bladder, hydrometrocolpos, and oligohydramnios - Chih-Ping Chen; Chen-Yu Chen; Jun-Wei Su; Wayseen Wang (Elsevier, 2013)
Objective: To present female pseudohermaphroditism in a prenatally diagnosed cloacal malformation. Case report: A 29-year-old, primigravid woman referred for counseling at 17 weeks of gestation because of oligohydramnios and an intra-abdominal cyst in the fetus. The woman was not exposed to any virilizing agent during this pregnancy. She did not undergo any assisted reproductive technology for this pregnancy. Level II ultrasound showed a singleton with fetal biometry equivalent to 16 weeks, oligohydramnios, hydrometrocolpos, dilated bladder, and bilateral hydronephrosis. A diagnosis of cloacal malformation was made. The parents elected to terminate the pregnancy at 18 weeks of gestation. A 196-g fetus was delivered with a distended abdomen, a phallus-like structure, a small perineal opening below the phallus-like structure, and an imperforate anus. At birth, the fetus was misdiagnosed as a male with an imperforate anus and a perineal fistula. Cytogenetic analysis of the cord blood revealed a karyotype of 46,XX. Array comparative genomic hybridization analysis of the fetal tissues revealed no genomic imbalance. The phallus-like structure was an enlarged clitoris and contained accessory phallic urethra. Conclusion: Prenatal diagnosis of cloacal malformation with ambiguous genitalia should be paid attention to avoid misdiagnosis of a male with an imperforate anus and a perineal fistula. Cytogenetic analysis is helpful to determine the sex under such circumstances.